Az „izgalmas és titokzatos példa”: A Lúdas Matyi-mesetípus szóbeli és írásbeli hagyományozódása - Gulyás, Judit (Studia Litteraria, 2020)
Lúdas Matyi (‘Matthew, the Goose Keeper, an original Hungarian tale’), an epic poem written by Mihály Fazekas in 1804 (published in 1815 and 1817 in Vienna), is the earliest known Hungarian variant of the tale type ATU 1538 (The Revenge of the Cheated Man). The poem has been interpreted as a pioneer work that introduced a peasant hero as well as the genre of the (despised) tale into Hungarian literature. Yet, hardly any variants of this tale type have been recorded from Hungarian oral tradition in the past two centuries. The author investigates this seeming contradiction, and analysing the eight oral variants as well as popular literacy argues that it was precisely the immense (written and theatrical) popularity of the plot that probably hindered the survival of an independent oral tradition of this tale.